International diversification strategies: Revisited from the risk perspective - Bai, Ye; Green, Christopher J. (Journal of Banking & Finance, 2010)
Following Roll [Roll, R., 1992. Industrial structure and comparative behaviour of international stock market indices. Journal of Finance 47, 3–42] and Heston and Rouwenhorst [Heston, S.L., Rouwenhorst, G.K., 1994. Does industrial structure explain the benefits of international diversification. Journal of Financial Economics 36, 3–27], researchers have decomposed stock returns into country and industry components. Evidence suggests that industry components have become more important in recent years, but the reasons for this are unclear. Existing research concentrated mainly on stock returns in industrial countries. In this paper we consider instead the decomposition of stock risks within emerging equity markets. We provide a rationale for this procedure and its relationship to return decompositions. The results provide new firm-specific evidence on the debate over country and industry components, their stability over time, and the implications for portfolio diversification.